Cetacean Poxvirus in Two Striped Dolphins (Stenella coeruleoalba) Stranded on the Tyrrhenian Coast of Italy: Histopathological, Ultrastructural, Biomolecular, and Ecotoxicological Findings - Cocumelli, Cristiano; Fichi, Gianluca; Marsili, Letizia; Senese, Matteo; Cardeti, Giusy; Cersini, Antonella; Ricci, Enrica; Garibaldi, Fulvio; Scholl, Francesco; Di Guardo, Giovanni; Terracciano, Giuliana (Frontiers in Veterinary Science, 2018)
Tattoo skin disease (TSD) is a poxviral disease typical of cetaceans. Two juvenile and well-preserved male striped dolphins (Stenella coeruleoalba), found stranded along the Tuscany and Latium coasts of Italy in 2015 and 2016, respectively, showed typical skin lesions ascribable to TSD. Histological, ultrastructural and biomolecular investigations confirmed a poxviral aetiology for the aforementioned skin lesions. To our knowledge, this should be the first report of TSD in cetaceans stranded along the Italian coastline. As organochlorines like PCBs and DDTs are known to be highly immunotoxic, the tissue loads of these contaminants were evaluated, in order to increase our knowledge on their potential role as well as on the relationships between the level of exposure to these pollutants and poxviral infection’s occurrence.